Five-Year Review of the Pattern of Semen Analysis among Male Partners of Infertile Couples at a Tertiary Health Facility in South-South Nigeria - Okiemute Madjemu; Aimiehinor Edward Akhator; Osamudia Okhionkpamwonyi; Innocent Okoacha (IPS Journal of Public Health, 2026)
Background: Infertility is a worldwide problem, affecting 15%-20% of couples in the reproductive age. Male factor infertility contributes a significant proportion of cases. Semen analysis has remained an objective, inexpensive and readily available means of assessing male factor infertility. Aim: This study aims to determine the prevalence of male infertility, the types and semen quality among infertile couples attending the gynaecological clinic in Tertiary health facility. Methods: This was a retrospective descriptive study involving male partners of infertile couples attending the gynaecological clinic between January 1st 2020 to December 31st 2024. Case notes of all eligible patients were retrieved and relevant information was extracted and analysed. Results: The prevalence of infertility was 8.3%. 7.3% had primary infertility while 62.4% had secondary infertility. 69.7% had abnormal semen parameters of which 51.1% had asthenospermia. Lifestyle modification and occupational hazard were contributory factors to the abnormal sperm parameters. Conclusion: Male factor infertility contributes significantly to the burden of infertility in our environment. Therefore, there is the need to create awareness so that males fully participate in the evaluation.